SAT0293 Safety and efficacy of tofacitinib, an oral janus kinase inhibitor, up to 36 months in patients with active psoriatic arthritis: data from the third interim analysis of opal balance, an open-label, long-term extension study. (12th June 2018) - Nash, P.; Coates, L.C.; Kivitz, A.J.; Mease, P.J.; Gladman, D.D.; Covarrubias-Cobos, J.A.; Fleishaker, D.; Wang, C.; Kudlacz, E.; Menon, S.; Fallon, L.; Hendrikx, T.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA). Objectives: To report the safety, tolerability and efficacy of tofacitinib in patients (pts) with active PsA from an ongoing, open-label, long-term extension (LTE) study (OPAL Balance, NCT01976364 ; November 2017 data-cut; database not locked). Methods: Eligible pts from 2 Phase (P)3 tofacitinib PsA studies (OPAL Broaden, NCT01877668 ; OPAL Beyond, NCT01882439 ) entered a 3 year LTE ≤3 months after completing the P3 study or discontinuing for reasons unrelated to study drug. Pts received tofacitinib 5 mg BID to Month (M)1, after which dose adjustments between 5 and 10 mg BID were permitted to improve efficacy, or for safety reasons. Pts receiving a csDMARD at P3 study entry continued the same csDMARD in the LTE. Primary endpoints were incidence and severity of adverse events (AEs) and changes from baseline (Δ) in laboratory values. Safety data are reported up to M36. Efficacy was evaluated up to M30 (when n>50) as a secondary endpoint. Results: 686 pts were treated in OPAL Balance; 468 (68.2%) remained in the study at data cut-off. Mean (range) LTE tofacitinib exposure was 614 (1–1032) days. On Day 1, 675 pts (98.4%) received a csDMARD, which was discontinued in 86 pts (12.7%). To M36, 2189 AEs were reported in 546 pts (79.6%), 95 pts (13.8%) had serious AEs and 59 pts (8.6%) discontinued due to AEs. Serious infections occurred in 12 pts (1.7%), herpes zoster (HZ) in 20 pts (2.9%; 1 serious event), major adverse cardiovascular events in 5 pts (0.7%), malignancies in 24 pts (3.5%; including 12 pts with NMSC) and uveitis in 2 pts (0.3%). No AEs of gastrointestinal perforation or inflammatory bowel disease were reported. There were 5 deaths (not attributed to treatment, as assessed by the investigator) due to metastatic pancreatic carcinoma, acute cardiac failure/hypertensive heart disease, chronic obstructive pulmonary disease, pulmonary embolism and cardiovascular insufficiency. Four AEs of latent tuberculosis were reported in pts whose previously negative QuantiFERON response became positive. ALT was elevated ≥3 x ULN in 27 pts (4.0%), and AST≥3 x ULN in 15 pts (2.2%). Changes in laboratory values observed in P3 studies were generally stable in the LTE, except for a modest decrease in absolute lymphocyte count over time. Eight pts (1.2%) discontinued (protocol-mandated) due to laboratory value changes. ACR responses, ΔHAQ-DI, PASI75 response, ΔLeeds Enthesitis Index, ΔDactylitis Severity Score and ΔPain were maintained up to M30. Conclusions: Over 36 months in the LTE, the safety profile of tofacitinib in active PsA pts was generally similar to that of the P3 studies. No new safety risks were identified. Efficacy across various PsA disease domains was maintained over time. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by A MacLachlan of CMC and funded by Pfizer Inc. Disclosure of Interest: P. Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, L. Coates Grant/research support from: AbbVie, Janssen, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer Inc, Sun Pharma, UCB, A. Kivitz Consultant for: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi, UCB, Speakers bureau: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi, UCB, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer Inc, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer Inc, Sun, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer Inc, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, J. Covarrubias-Cobos Grant/research support from: Bristol-Myers Squibb, Eli Lilly, Janssen, Pfizer Inc, D. Fleishaker Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc